Characterization of antidiabetic activity of silver nanoparticles using aqueous solution of Ficus glomerata (FIG) gum - MERINA PAUL DAS; L.JEYANTHI REBECCA (International Journal of Pharma and Bio Sciences, 2017)
Current discovery demonstrates the facile and rapid synthesis of biocompatible silver nanoparticles (AgNPs) by a novel biological route using aqueous solution of fig gum (Ficus glomerata). These silver nanoparticles were characterized by means of UV–vis spectroscopy, scanning electron microscopy (SEM), electron diffraction spectroscopy (EDX) and X-ray diffraction (XRD). The nanoparticles exhibited maximum absorbance at 408 nm in UV–vis spectroscopy. The XRD spectrum of silver nanoparticles exhibited 2θ values corresponding to the silver nanocrystals. SEM micrographs revealed the formation of well-dispersed silver nanoparticles of 31 nm in an average size, and the presence of silver was confirmed by EDX analysis. This in vitro study explores the antidiabetic properties of biosynthesized silver nanoparticles and it can be considered as a potential candidate for the management of type-II diabetes mellitus. The assay results of silver nanoparticles showed a dose dependent pattern. The percentage inhibitory activity significantly increase against α-amylase (alpha amylase) enzyme, 95.28 ± 0.33 % inhibition was seen at a concentration of 50 μg/ml and 97.74 ± 0.3 % inhibition was observed at 1000 μg/ml, similarly against α-glucosidase (alpha glucosidase) enzyme, the enzyme inhibition was observed at lower concentration of 50 μg/ml, 97.14 ± 0.02 % of inhibition and 99.98 ± 0.61 % inhibition at higher concentration of 1000 μg/ml was recorded. The results of the study also revealed that the antidiabetic activity of the AgNPs is much higher than the standard antihyperglycemic drug.